Keeping the faith : a history of northern soul - Catterall, Stephen John; Gildart, Keith (Manchester University enk Press, 2020)
This book examines the development of northern soul, its clubs, publications, and practices by locating it in the shifting economic and social context of the English midlands and north in the 1970s. Using fanzines, diaries, letters, and oral testimony it presents a vivid insight into the scene. It makes a major contribution to our understanding of the connections between class and music in post-war Britain.